TEACHING WRITING THROUGH PICTURE FOR JUNIOR HIGH SCHOOL STUDENTS - Leonardo, Pebri; Saragih, Dhea; Sibatuara, Rinto; Silaen, Meichel (Transpublika Publisher, 2022)
This research was conducted with the aim of finding the usefulness and benefits of picture as a teaching strategy or media of teaching to teach writing skill to the students. The method in this research was classroom action research method, which was carried out in two cycles. Subjects or participants in this study were the students at SMP Negeri 7 Pematangsiantar, precisely the IX-4 students. The researchers collected data from the test results of students on the implementation of picture in writing a text. In addition, the data were also obtained through observation results carried out in the learning process. Based on the results of research that the researchers obtained, it was proven that the use of picture had effects on student learning abilities. Their writing abilities increased after using pictures as medium in writing a text.